Human podocytes perform polarized, caveolae-dependent albumin endocytosis - Dobrinskikh, Evgenia (American Physiological Society, 2014)
The renal glomerulus forms a selective filtration barrier that allows the passage of water, ions, and small solutes into the urinary space while restricting the passage of cells and macromolecules. The three layers of the glomerular filtration barrier include the vascular endothelium, glomerular basement membrane (GBM), and podocyte epithelium. Podocytes are capable of internalizing albumin and are hypothesized to clear proteins that traverse the GBM. The present study followed the fate of FITC-labeled albumin to establish the mechanisms of albumin endocytosis and processing by podocytes. Confocal imaging and total internal reflection fluorescence microscopy of immortalized human podocytes showed FITC-albumin endocytosis occurred preferentially across the basal membrane. Inhibition of clathrin-mediated endocytosis and caveolae-mediated endocytosis demonstrated that the majority of FITC-albumin entered podocytes through caveolae. Once internalized, FITC-albumin colocalized with EEA1 and LAMP1, endocytic markers, and with the neonatal Fc receptor, a marker for transcytosis. After preloading podocytes with FITC-albumin, the majority of loaded FITC-albumin was lost over the subsequent 60 min of incubation. A portion of the loss of albumin occurred via lysosomal degradation as pretreatment with leupeptin, a lysosomal protease inhibitor, partially inhibited the loss of FITC-albumin. Consistent with transcytosis of albumin, preloaded podocytes also progressively released FITC-albumin into the extracellular media. These studies confirm the ability of podocytes to endocytose albumin and provide mechanistic insight into cellular mechanisms and fates of albumin handling in podocytes.